Ijarah dalam Sistem Perbankan Syariah - Fitriani, Dara; Nazaruddin, Nazaruddin (Al-Hiwalah: Journal of Sharia Economic Law, 2022)
Lease transactions in conventional banking do not transfer property rights, which means that when the lease expires, the goods are returned to the owner of the leasing object, which generally does not require the services of a financial institution. Another case in practice is because of Islamic banking financing which is known under a lease agreement called ijarah. In Islamic banking, al-ijarah is divided into 2 types, namely mutlaqah ijarah or leasing, operating lease is a process that we usually encounter in daily economic activities. In the context of Islamic banking, ijarah is a lease contract in which a bank or financial institution rents out equipment, buildings or goods, to one of its customers by charging a fee that has been determined with certainty in advance. Meanwhile, al-Ijarah al-Muntahia bit-Tamlik is a kind of fusion between a sales and lease contract or a lease contract which ends with the ownership of the goods being in the hands of the lessee. The nature of the transfer of ownership also distinguishes it from ordinary leases, which exist in conventional financial institutions. The concept of al-Ijarah in Islamic banking as a lease in general, but what distinguishes it is that in Islamic banking there is a lease which at the end of the contract, the customer is given a choice/option to own the goods or not, generally called a lease purchase.